Hemodynamic activation of von Willebrand factor in children with congenital heart diseases - K. A. Tokmakova; D. N. Shilkin; A. A. Kupryashov (Акушерство, гинекология и репродукция)
Quite complex and non-linear cellular and molecular mechanisms underlie hemostasis changes in patients with congenital heart diseases (CHD). Altered activity ratio between von Willebrand factor (vWF) and metalloproteinase ADAMTS-13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13) is of pathogenetic significance. The high rate of vWF exocytosis, emergence of its multimeric soluble plasma forms and high rate of proteolysis to small counterparts along with ADAMTS-13 consumption lead to a affected the vWF/ADAMTS-13 axis resulting in hemostasis-related prothrombogenic potential. vWF activity depends on the hydrodynamic characteristics in intravascular blood flow. The magnitude of shear stress in CHD promotes a high rate of conformational changes in vWF multimer, thereby suggesting that hemodynamic conditions may determine developing hemostasis alterations.